Determinants promoting and hindering physical activity in primary school children in Germany: a qualitative study with students, teachers and parents - Sell, Louisa; Brandes, Berit; Brandes, Mirko; Zeeb, Hajo; Busse, Heide (Frontiers in Public Health, 2024)
Determinants affecting children's physical activity (PA) at an early age are of particular interest to develop and strengthen strategies for increasing the levels of children's PA. A qualitative study was conducted to investigate the views of primary school-aged children, their teachers and parents regarding barriers and facilitators to engage in PA.Focus groups were conducted separately with primary school children, parents and teachers in a city in Northern Germany between October 2021 and January 2022. The semi-structured focus groups with children and teachers took part in person within school, whereas the focus groups with parents took place online. Data were transcribed verbatim and analysed using thematic analysis.During analysis, the socio-ecological model (Bronfenbrenner, 1979) was identified as useful to map the determinants mentioned and was consequently applied to organize the data.